Coaches` insights: Determinants of athlete success, physical demands and training approaches in single-handed Olympic-class dinghy sailing - Winchcombe, C. E.; Goods, P. S. R.; Binnie, M. J.; Peeling, P. (PLOS ONE, 2025)
Gaining insights into experienced coaches` perceptions and understanding of performance and training can enhance knowledge to optimise athlete performance. Ten experienced International Laser Class Association dinghy (ILCA) sailing coaches with world-class and elite ILCA coaching credentials undertook semi-structured interviews to explore three key topic areas: i) determinants of athlete success, ii) physical demands of competition, and iii) training practices and philosophies. Hierarchical content analysis was used to establish general dimensions and higher order themes from the interview transcripts. Three general dimensions were established within the topic area of determinants of athlete success: i) sailing the boat fast, ii) being a knowledgeable athlete, and iii) consistent execution. Within the topic area of physical demands of competition three general dimensions were also developed: i) hiking is the most physically demanding skill, ii) environmental conditions influence athletic demands, and iii) accumulation of fatigue over a regatta. Finally, in the topic area of training practices and philosophies there were two general dimensions: i) periodisation, and ii) specific training. Overall, hiking featured across all three topic areas, highlighting its importance in ILCA sailing. Additionally, `feel` and `keeping the joy` were identified as higher order themes that have been under-researched in current literature. Findings suggest coaches should target consistency in both on and off-water training through `keeping the joy` and sailing in a variety of conditions to improve aspects such as `feel` and `pattern recognition`. We provide key insights into components of performance and aspects of the physical demands and training in ILCA sailing to optimise athlete performance.